Substitution Study for Cost Effective Hybrid Power System using Power Pinch Analysis - Mustapha, Nur Nadiah (Universiti Teknologi PETRONAS, 2016)
Issues with the imbalance of supply and demand as well as the increasing emission of carbon dioxide have led to the advancement of other alternatives to generate power based on renewable energy (RE). However, implementing RE for power generation in hybrid power system (HPS) is a challenging task. The technology of RE is known to be upscale and RE resources especially solar and wind are highly-dependent on weather and climate conditions. The objective of this research is to design a cost-effective HPS using Power Pinch Analysis and the substitution strategy from Systematic Hierarchical Approach for Cost-Screening Technique (SHARPS). Modified Storage Cascade Table (SCT) which is one of Power Pinch Analysis method was constructed to find the minimum electricity target which was used to analyse the investment cost per saving of RE generation technologies involved.